PENGARUH ATRIBUT PRODUK CITRA HAND & BODY LOTION TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN DI KOTA JEMBER - Robustin, Tri Palupi (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: This research aims to examine and analyze the influence of: (1) product attributes on customer satisfaction, (2) product attributes on customer loyalty, and (3) satisfaction on customer loyalty of Citra Hand & Body Lotion product in Jember. Structural Equation Modeling analysis with AMOS 18 program was used to test the hypothesis. The sample consisted of 110 respondents. Results showed that: (1) product attributes had positive and significant effect on customer satisfaction, (2) product attributes had positive and significant effect on customer loyalty, and (3) satisfaction had positive and significant effect on customer loyalty of Citra Hand and Body Lotion product in Jember. Keywords: Product Attributes, Satisfaction, Customer Loyalty.